Sing backwards and weep : a memoir - Lanegan, Mark (Hachette Books, 2020)
"A gritty, gripping memoir by the singer Mark Lanegan (Screaming Trees, Queens of the Stone Age, Soulsavers), chronicling his years as a singer and drug addict in Seattle in the '80s and '90s"--